IN VITRO MATURATION OF BUBALINE OOCYTES USING BUBALINE (SWAMP BUFFALO) FOLLICULAR FLUID - Aquino, Flocerfida P.; Ocampo, Marlon B. (Proceeding Buffalo International Conference, 2013)
The mammalian ovaries are valuable source of oocytes for reproductive biotechnology. Oocytes attain developmental competence in vivo being in follicular fluid so using it as maturation medium could be an option. Pig and bovine IVM studies using follicular fluid gave favorable effects. Bubaline IVM experiment in CRD made use of 271 oocytes from buffalo ovaries. The oocytes were subjected to five maturation media: pure TCM 199 (T 1); 50% TCM 199 + 50% BFF from 2-5 mm follicle size (FS) (T 2); pure BFF from 2-5mm FS (T 3); 50% TCM 199 + 50% BFF from 5-8mm FS (T 4) and pure BFF from 5-8 mm FS (T 5). The oocytes were cultured for 22-24 hours at 38oC, 5% CO2 in air and high humidity inside the incubator then the oocytes were fixed, stained destained and evaluated their developmental competence. In all the treatments, no significant differences were observed in the IVM stages of bubaline oocytes. The percentage values of matured oocytes ranged from 64.44% to 79.72%. The size of the follicles used in Treatments 2 and 3 showed no significant variations on oocyte maturation from Treatments 4 and 5. Â BFF can be a substitute for TCM 199 in pure form or in combination with TCM 199 in bubaline IVM studies.